Enzymatic Labeling of Bacterial Proteins for Super-resolution Imaging in Live Cells - Ho, Samuel H. (ACS Cent Sci, 2019)
[Image: see text] Methods that enable the super-resolution imaging of intracellular proteins in live bacterial cells provide powerful tools for the study of prokaryotic cell biology. Photoswitchable organic dyes exhibit many of the photophysical properties needed for super-resolution imaging, including high brightness, photostability, and photon output, but most such dyes require organisms to be fixed and permeabilized if intracellular targets are to be labeled. We recently reported a general strategy for the chemoenzymatic labeling of bacterial proteins with azide-bearing fatty acids in live cells using the eukaryotic enzyme N-myristoyltransferase. Here we demonstrate the labeling of proteins in live Escherichia coli using cell-permeant bicyclononyne-functionalized photoswitchable rhodamine spirolactams. Single-molecule fluorescence measurements on model rhodamine spirolactam salts show that these dyes emit hundreds of photons per switching event. Super-resolution imaging was performed on bacterial chemotaxis proteins Tar and CheA and cell division proteins FtsZ and FtsA. High-resolution imaging of Tar revealed a helical pattern; imaging of FtsZ yielded banded patterns dispersed throughout the cell. The precision of radial and axial localization in reconstructed images approaches 15 and 30 nm, respectively. The simplicity of the method, which does not require redox imaging buffers, should make this approach broadly useful for imaging intracellular bacterial proteins in live cells with nanometer resolution.